THE PRACTICE-ORIENTED TRAINING OF FUTURE ELEMENTARY SCHOOL TEACHER - Ivaniuk, Hanna I.; Demianenko, Valentina I. (Educological discourse, 2016)
This article highlights some aspects of practice-oriented training of future teacher of primary school teachers in the study of pedagogical subjects. The practice-oriented (raining of primary school teachers see as a system based on the fact that education is the result of a focused, organized, planned mastering a subject of future teachers, together elements of the system of objective human experience and social acceptance has on educational qualification of professional training. The purpose of the article is to highlight features of practice-oriented training of future teacher in primary school in teaching pedagogical subjects. While working on the article studied the issue of professional training of future elementary school teacher, raised in studies Ukrainian and foreign scientists. Outlined problem is considered in the context of active, personal, competency approaches. It was found that the practice-oriented training future teachers provided targeted sampling objective experience, learning in the process of training and formation of new educational quality. The article deals with the essential features of the project technology with regard to progress in stages. Method of projects consider due to the fact that it enables the implementation of effective practice-oriented training of future elementary school teacher. Posted author's experience in the use of educational projects, disciplines "Fundamental: of Education" and "Theory and Methods of Education. "Results of seeking ways practice oriented training students field of study "Primary education" for professional work in project technology have both scientific and practical significance. The essence of the algorithm and the implementation of technology projects in the practice of the educational process of higher education. The implementation of educational projects with pedagogical disciplines enables upload of future primary school teachers to practice. Especially a cost component of the project is the motivation of the individual which promotes spiritual and moral formation of future teachers.